Ohthe places you'll go - Seuss, Dr. (London : Harper Collins Children's Books, 1990)
A city of Whos on a speck of dust are threatened with destruction until the smallest Who of all helps convince Horton's friends that Whos really exist.
Keywords: Imagination -- Juvenile fiction; Success -- Fiction; Stories in rhyme